2015
DOI: 10.1177/0307174x1504200106
|View full text |Cite
|
Sign up to set email alerts
|

Calculating the Thermal Conductivity of Filled Fluoroplastics by Methods of Generalised Conductivity Theory

Abstract: An examination was made of the potential use of analytical methods of generalised conductivity theory for the interpolation and extrapolation of the results of measurements and prediction of the effective thermal conductivity of composite materials-fluoroplastics with different powder fillers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Lu’s group prepared a series of CVD-3DGM-assisted TIMs with high thermal performance, and the thermal conductivity reached 14.6 W m −1 K −1 after adding ∼10 wt-% CVD-3DGM, which is more than 50 times higher than that of the pure ER [87]. Zhao et al found that 0.7 wt-% additional CVD-3DGM gives a conspicuous enhancement (300%) for the thermal conductivity of polydimethylsiloxane (PDMS), which is 20% higher than that of RGO nanosheets-assisted sample [88]. Compared with that of RGO nanosheets and RGO-3DGM-added TIMs, the better thermal performance of the CVD-3DGM-modified samples is resulting from the presence of a complete heat transport network and the absence of an additional adhesive.…”
Section: Performances Of the 3dgm-based Compositesmentioning
confidence: 99%
“…Lu’s group prepared a series of CVD-3DGM-assisted TIMs with high thermal performance, and the thermal conductivity reached 14.6 W m −1 K −1 after adding ∼10 wt-% CVD-3DGM, which is more than 50 times higher than that of the pure ER [87]. Zhao et al found that 0.7 wt-% additional CVD-3DGM gives a conspicuous enhancement (300%) for the thermal conductivity of polydimethylsiloxane (PDMS), which is 20% higher than that of RGO nanosheets-assisted sample [88]. Compared with that of RGO nanosheets and RGO-3DGM-added TIMs, the better thermal performance of the CVD-3DGM-modified samples is resulting from the presence of a complete heat transport network and the absence of an additional adhesive.…”
Section: Performances Of the 3dgm-based Compositesmentioning
confidence: 99%